Prioritized Expression of BDH2 under Bulk Translational Repression and Its Contribution to Tolerance to Severe Vanillin Stress in Saccharomyces cerevisiae - Ishida, Yoko; Nguyen, Trinh T. M.; Kitajima, Sakihito; Izawa, Shingo (Frontiers in Microbiology, 2016)
Vanillin is a potent fermentation inhibitor derived from the lignocellulosic biomass in biofuel production, and high concentrations of vanillin result in the pronounced repression of bulk translation in Saccharomyces cerevisiae. Studies on genes that are efficiently translated even in the presence of high concentrations of vanillin will be useful for improving yeast vanillin tolerance and fermentation efficiency. The BDH1 and BDH2 genes encode putative medium-chain alcohol dehydrogenase/reductases and their amino acid sequences are very similar to each other. Although BDH2 was previously suggested to be involved in vanillin tolerance, it has yet to be clarified whether Bdh1/Bdh2 actually contribute to vanillin tolerance and reductions in vanillin. Therefore, we herein investigated the effects of Bdh1 and Bdh2 on vanillin tolerance. bdh2∆ cells exhibited hypersensitivity to vanillin and slower reductions in vanillin than wild-type cells and bdh1∆ cells. Additionally, the overexpression of the BDH2 gene improved yeast tolerance to vanillin more efficiently than that of BDH1. Only BDH2 mRNA was efficiently translated under severe vanillin stress, however, both BDH genes were transcriptionally up-regulated. These results reveal the importance of Bdh2 in vanillin detoxification and confirm the preferential translation of the BDH2 gene in the presence of high concentrations of vanillin. The BDH2 promoter also enabled the expression of non-native genes under severe vanillin stress and furfural stress, suggesting its availability to improve of the efficiency of bioethanol production through modifications in gene expression in the presence of fermentation inhibitors.